2018
DOI: 10.1111/jnc.14345
|View full text |Cite
|
Sign up to set email alerts
|

The GABAergic system as a therapeutic target for Alzheimer's disease

Abstract: Glutamatergic and cholinergic dysfunction are well-attested features of Alzheimer's disease (AD), progressing with other pathological indices of the disorder and exacerbating neuronal and network dysfunction. However, relatively little attention has been paid to the inhibitory component of the excitatory/inhibitory (E/I) network, particularly dysfunction in the gamma-aminobutyric acid (GABA) signaling system. There is growing evidence in support of GABAergic remodeling in the AD brain, potentially beginning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 229 publications
(518 reference statements)
3
80
0
1
Order By: Relevance
“…Such a possibility is consistent with data suggesting that impaired GABAergic neurotransmission occurs early in AD and with data from animal studies of AD mouse models demonstrating beneficial effects of GABAergic agonists on cognition (Calvo-Flores et al, 2018). Our ReHo analyses revealed increased synchronous activity in the temporal cortex and AAC, brain regions known to be affected in AD.…”
Section: Discussionsupporting
confidence: 87%
“…Such a possibility is consistent with data suggesting that impaired GABAergic neurotransmission occurs early in AD and with data from animal studies of AD mouse models demonstrating beneficial effects of GABAergic agonists on cognition (Calvo-Flores et al, 2018). Our ReHo analyses revealed increased synchronous activity in the temporal cortex and AAC, brain regions known to be affected in AD.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with this concept, antiepileptic drugs mainly targeted on the glutamatergic system, such as levetiracetam (Sanchez et al, ), have been used to compensate the excess of excitation, although with limited success (Vossel et al, ). Consequently, inhibitory neurotransmission systems have gained great interest in recent years, not only as potential pharmacological targets, but also as part of combinational therapies that might synergistically protect neuronal degradation in AD (Calvo‐Flores Guzman et al, ; Nava‐Mesa et al, ). One interesting example is the combined drug therapy using the NMDA‐receptor antagonist, acamprosate and the GABA B agonist, baclofen (Hill & Bowery, ) whose main effector is the GirK channel, with significant benefits over monotherapeutics (Chumakov et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the indexes for temporal-scale-dependent complexity has shown that this reduction of complexity especially concentrates in fast wave components (34,36). Studies of neurotransmitter changes in AD have reported that dysfunction of the gamma-aminobutyric acid (GABA) signaling system, which is caused by the deposition of amyloid-b and tau proteins, leads to reduced oscillatory gamma band activity (68)(69)(70). The impairment of gamma oscillatory activity might lead the complexity at faster temporal scales more than slower temporal scales (34,36).…”
Section: Discussionmentioning
confidence: 99%